Fast-Track Extubation in a Patient Undergoing Whole Lung Lavage: A Case Report - Gade Sandeep; Subrata K. Singha; Anil Gupta; Keerthi Chinnadurai; Harishchandra Gupta (Annals of Cardiac Anaesthesia)
Pulmonary alveolar proteinosis (PAP) is a rare pulmonary pathology characterized by the accumulation of surfactant within type II alveolar epithelial cells. Whole lung lavage is the standard treatment for pulmonary alveolar proteinosis involving a large volume of fluid is infused into one lung and subsequently retrieved while the other lung is remains ventilated. Fast-tracking a patient undergoing whole lung lavage requires vigilant monitoring of arterial blood gases, fluid status, and respiratory mechanics. We report a case of a patient who underwent whole lung lavage for PAP, where early extubation was performed, avoiding the complications associated with prolonged mechanical ventilation.